Leadership: an effective human factor during COVID-19. Issue 3 (12th August 2021) - Dhahri, Adeel Abbas; Refson, Jonathan
Abstract : Background: A hybrid leader is an individual with a professional background who takes on managerial roles. For surgeons, leadership is a non-technical skill within a domain of a human factor and a diverse role that makes them an effective hybrid leader. Objectives: We hypothesised that a surgical leader acts as a link between different departments in an organisation to influence performance at the workplace to bring positive changes in healthcare and patient safety. Methods: We followed the nine-dimension Healthcare Leadership Model (HLM) and reflected on the leadership roles within our surgical department at the Princess Alexandra Hospital NHS Trust, United Kingdom. Results: Changes were quickly adopted and monitored while leadership learned adaptability to function quickly. Hierarchical decision making was removed while levelling up communication. Telemedicine was quickly adopted at both elective and ambulatory emergency settings. The local survey also showed trust and co-operation among team members. Conclusions: Hybrid surgical leadership is a complex but divergent role that acts as a bridge between the surgical team and others in administrative roles that promotes safer patient outcomes and better well-being for the organisations' members